2015
DOI: 10.19045/bspab.2015.43005
|View full text |Cite
|
Sign up to set email alerts
|

Cultural conditions for maximum alphaamylase production by Penicillium notatum IBGE 03 using shaken flask technique of submerged fermentation

Abstract: Cultural conditions for maximum Alpha-Amylase production by Penicillium notatum IBGE 03 using shaken flask technique of submerged fermentation. AbstractEver increasing biotechnological industries require an enlarged survey of microorganisms which might be useful for industries. In the present work optimization parameters for alpha amylase production by Penicillium notatum IBGE 03 in submerged fermentation were studied. Various agricultural based by-products (sunflower waste, cotton stalk, rice husk, date syrup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“… 49 The optimized pH for the production of alpha-amylase by Penicillium notatum IBGE 03 has been reported to be 5.5. 42 Also, Bacillus sp. MB6 produces a remarkable quantity of alpha-amylase at pH 6.…”
Section: Alpha-amylase Productionmentioning
confidence: 99%
See 3 more Smart Citations
“… 49 The optimized pH for the production of alpha-amylase by Penicillium notatum IBGE 03 has been reported to be 5.5. 42 Also, Bacillus sp. MB6 produces a remarkable quantity of alpha-amylase at pH 6.…”
Section: Alpha-amylase Productionmentioning
confidence: 99%
“…The digestive activity of alpha-amylases is measured via several colorimetric methods, including dinitrosalicylic acid method (DNS), Nelson-Somogyi, and Iodine method. 42 DNS is an alkaline reagent that attaches to the reducing sugars and then color changes can be detected by UV absorbance at 540 nm 43 (Figure 1). Amylases, xyloglucanases, pectinases, and β-mannanases are assessed by DNS method.…”
Section: Enzyme Activity Assaymentioning
confidence: 99%
See 2 more Smart Citations
“…and Brevibacillus borstelensis R1 (Singh et al 2012, Suribabu et al 2014. The production optimization studies showed that maximum enzyme production by Penicillium notatum IBGE 03 was obtained at pH 5.5 (Ahmed et al 2015). In neutral conditions (pH 6.5-7.5), the α-amylase production was reported in Bacillus sp.…”
Section: Discussionmentioning
confidence: 97%